Exploring nature-based tourism and visitor learning at in situ and ex situ destinations - Bueddefeld, Jill (2019)
This research was guided by the following research questions: (1) How does an experience in Churchill, Manitoba (in situ) and at the Assiniboine Park Zoo’s (APZ) Journey to Churchill Exhibit (ex situ) impact learning and behaviour change / transformative learning? (2) Additionally, what role does place (in situ versus ex situ) play in influencing the visitor experience, particularly in relation to learning and behaviour change / transformative learning? This qualitative study is grounded in Constructivist Learning Theory and Transformative Learning Theory (TLT) and is guided by the Contextual Model of Learning (CML). Approximately 30 participants at each site completed personal meaning maps and interviews on-site and post-visit, to examine changes in learning as well as potential impacts of perceptions of authenticity and visitor qualities, such as motivations. A comparative content analysis examined visitor learning at two sites: Churchill, Manitoba (in situ) and the Assiniboine Park Zoo’s Journey to Churchill Exhibit (ex situ) in Winnipeg, Manitoba. This research found that segmenting visitors by Falk’s visitor motivation related identities was effective for understanding visitor experiences and learning - more so than comparing in situ and ex situ visitors alone. Transformative learning was illustrated at both sites, especially for visitors with learning centric motivations. Transformative learning that was epochal and facilitated by a disorienting dilemma was unique to a few in situ visitors. However, ex situ visitors were more easily able to identify behaviours that they had changed as attributed to their on-site experiences. This research merges the fields of free-choice learning and TLT by proposing a model which integrates the contexts of the CML with TLT domains and provides practitioners and researchers with insight into designing and assessing potentially transformative learning experiences. Contrary to prior research, visitors at both sites did not demonstrate place attachment or a strong sense of ...